Vitamin D status in infancy: What is the solution? - Celep, Gökçe; Durmaz, Zeynep Hülya; Dörtok Demir, Hatice; Erdoğan, Yalçıner (Journal of Surgery and Medicine, 2019)
Aim: Vitamin D deficiency and insufficiency are common public health problems throughout the world. Besides important multisystemic metabolic effects, vitamin D is necessary for a healthy skeletal system. Various reasons cause vitamin D deficiency in infancy, and supplementation is one of the treatment options. A nationwide supplementation program has been implemented in Turkey since 2005. In this study, we aimed to evaluate the efficacy of this program in our city. Methods: All infants aged between one and twelve months who were referred to the pediatric outpatient clinics of the hospital and tested for serum 25-(OH)-D levels between January 1, 2015 and December 31, 2016 were enrolled in the study. Patients with chronic illnesses were excluded. Data was obtained retrospectively from the hospital registry. In accordance with the criteria of American Academy of Pediatrics, patients were divided into three groups based on serum 25-(OH)-D levels as follows: 25-(OH)-D<15 ng/ml were considered deficient, 15.1<25-(OH)-D<20 ng/ml were considered insufficient and sufficiency was defined as 25-(OH)-D>20 ng/ml. Results: The study group consisted of 265 infants. The mean age of the group was 7.53 (2.75) months. Approximately 15% (n=39) of the study group had vitamin D deficiency, 10.5% (n=28) had insufficiency and Vitamin D levels of 74.4% (n=198) of the group were sufficient. Serum 25 (OH) D levels did not differ with gender, age or season (P=0.12, P=0.65 and P=0.09, respectively). Vitamin D levels were sufficient in 78.5% (n=150) of the urban area residents and 69.6% (n=32) of the rural area residents, between which there was no significant difference (P=0.32). Conclusion: Our results established that supplementation is one of the ways to avoid limitations affecting serum vitamin D levels. Supplementation with 400 IU/day Cholecalciferol is provided during the first year of life by the Turkish Ministry of Health, which we believe rendered gender, age, time of measurement and residential area insignificant in terms of 25(OH) D levels. This supplementation program may solve the problem of vitamin D insufficiency or deficiency among disadvantaged groups.